Social imaginaries of subsea cables: recovering connections between Broome and Banyuwangi - Kerr, Thor; Wahyudi, I. (2021)
As most data travel through subsea cables, this article investigates social imaginaries of the cable laid in 1889 from Banyuwangi in south-eastern Java to Broome in north-western Australia. Through collaborative fieldwork in Broome and Banyuwangi, radically different representations are identified at either end of the cable. In Broome, the cable telegraph station is memorialized for introducing colonial sophistication to a town where Java is celebrated for facilitating communication with Britain. In Banyuwangi, there is no mention of Broome and little mention of the undersea cable. Instead, there are mythical and haunted representations of a decrepit British Hostel occasionally associated with telegraph operations. Despite some similarities in Indigenous perspectives and entrepreneurial desire to realize tourism income from cable heritage, an ocean-size gulf was identified between the social imaginaries that enabled the cable to be dug up and normalized as a cultural attraction in Broome while remaining buried, almost forgotten, in Banyuwangi.